EarthN: A New Earth System Nitrogen Model. (17th August 2018) - Johnson, Benjamin W.; Goldblatt, Colin
Abstract: The amount of nitrogen in the atmosphere, oceans, crust, and mantle have important ramifications for Earth's biologic and geologic history. Despite this importance, the history and cycling of nitrogen in the Earth system is poorly constrained over time. For example, various models and proxies contrastingly support atmospheric mass stasis, net outgassing, or net ingassing over time. In addition, the amount available to and processing of nitrogen by organisms is intricately linked with and provides feedbacks on oxygen and nutrient cycles. To investigate the Earth system nitrogen cycle over geologic history, we have constructed a new nitrogen cycle model: EarthN. This model is driven by mantle cooling, links biologic nitrogen cycling to phosphate and oxygen, and incorporates geologic and biologic fluxes. Model output is consistent with large (2‐4x) changes in atmospheric mass over time, typically indicating atmospheric drawdown and nitrogen sequestration into the mantle and continental crust. Critical controls on nitrogen distribution include mantle cooling history, weathering, and the total Bulk Silicate Earth + atmosphere nitrogen budget. Linking the nitrogen cycle to phosphorous and oxygen levels, instead of carbon as has been previously done, provides new and more dynamic insight into the history of nitrogen on the planet. Plain Language Summary: The history of nitrogen on Earth is poorly known, despite its importance in the atmosphere and for life to flourish. Here, we present a new model that describes how nitrogen moves through the atmosphere, biosphere, and geosphere over time. We find that, in contrast to the usual interpretation, large‐scale changes in atmospheric mass and nitrogen distribution through time are possible. This model provides a jumping‐off point for further predictions and explorations of this exciting element over Earth history. Key Points: We model the evolution of nitrogen in all the reservoirs of Earth Total, non‐core N and plate tectonics exert strong control on atmospheric mass Weathering and the Great Oxidation event cause atmospheric draw‐down